Formation of β-alumina in CuO. Al2O3. Na2O System - M. Selim, M.; F. R. Fouda, M.; S. Amin , R.; Abdel-Fattah, Wafa I. (Asian Journal of Chemistry, 2010)
The effect of doping by varying amounts of sodium ions (as sodium hydroxide) being 2, 5 and 10% on previousiy heated CuO.Al2O3 mixtures having molar ratios of 0.25 : 1, 0.5 : 1 and 1 : 1 was studied. The nine CuO.Al2O3.Na2O mixtures were calcined at 900ºC. Their structural characteristics were assessed through XRD analysis and complemented by IR spectral data. Accompanying morphological changes were followed through scanning electron microscopy. The calcination of the mixes produced powders with α-alumina, copper aluminate and/or copper oxide, depending on the copper content, beside the formation of abundant β-alumina. Fibrous β-alumina was obtained with the lowest CuO : Al2O3 molar ratio (0.25 : 1) with the 5% Na+ doping corresponding to 1 : 10 Na2O : Al2O3. With higher sodium content (10%), corresponding to 1 : 3–5 Na2O : Al2O3 as well as higher molar ratio of CuO : Al2O3 (0.5 : 1), (1 : 1) platy ,β-alumina was obtained. Such changes were correlated with coordination number of aluminium and the number of coordinated water species in the lattice.